“Clarity is a Fiction Made of the Fabric of Chaos”: Irzykowski Nonunderstandableness - Panek, Sylwia (Zagadnienia Rodzajów Literackich, 2019)
https://doi.org/10.26485/ZRL/2018/61.3/5 Artykuł w języku angielskim